Early Versus Delayed Mobilization Postoperative Protocols for Lateral Ankle Ligament Repair: A Systematic Review and Meta-analysis. Issue 6 (20th June 2020) - Vopat, Matthew L.; Tarakemeh, Armin; Morris, Brandon; Hassan, Maaz; Garvin, Pat; Zackula, Rosey; Mullen, Scott; Schroeppel, John Paul; Vopat, Bryan G.
Background: The majority of patients with an acute lateral ankle ligamentous injury are successfully treated nonoperatively with functional rehabilitation; however, a small proportion of these patients experience persistent chronic instability and may require surgical intervention. Delayed primary repair of the ruptured ligaments is most commonly indicated for these patients. Optimal rehabilitation after lateral ankle ligament repair remains unknown, as surgeons vary in how they balance protection of the surgical repair site with immobilization against the need for ankle joint mobilization to restore optimal postoperative ankle range of motion. Purpose: To compare early and delayed mobilization (EM and DM, respectively) postoperative protocols in patients undergoing primary lateral ankle ligament repair to determine optimal evidence-based rehabilitation recommendations. Study Design: Systematic review; Level of evidence, 4. Methods: Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a meta-analysis using the PubMed/Ovid MEDLINE database was performed (October 11, 1947 to October 16, 2017), searching for articles involving lateral ankle ligament repair. Postoperative protocols were reviewed and divided into 2 categories: EM (within 3 weeks of surgery) and DM (more than 3 weeks post surgery). Return to sport (RTS), outcome scores (American Orthopaedic Foot and Ankle Society [AOFAS] ankle-hindfoot scale and Karlsson score), radiographic outcomes (talar tilt and anterior drawer), and complications of both populations were recorded and statistically analyzed. Results: A total of 28 of 1574 studies met the criteria for the final analysis, comprising 1457 patients undergoing primary lateral ankle ligament repair. The postoperative AOFAS score was significantly greater in the EM versus DM group (98.8 vs 91.9, respectively; P < .001), as was the postoperative Karlsson score (92.2 vs 90.0, respectively; P < .001). However, the EM group had significantly greater postoperative laxity on both the anterior drawer test (6.3 vs 3.9 mm, respectively; P < .001) and talar tilt test (5.1° vs 4.5°, respectively; P < .001). Also, the DM group had significantly lower rates of overall complications (3.1% vs 11.4%, respectively; P < .001) and skin wound complications (1.3% vs 3.8%, respectively; P = .005). RTS was not significantly different between groups ( P = .100). Conclusion: Patients with EM postoperative protocols demonstrated improved functional outcomes; however, the EM group had increased objective laxity and a higher complication rate. Additional randomized studies are needed to definitively evaluate early versus delayed rehabilitation protocol timetables to optimize functional outcomes without compromising long-term stability.